Managing Ultrasonography in Human Reproduction : A Practical Handbook - Guerriero, Stefano; Martins, Wellington P.; Alcazar, Juan Luis (Springer International Publishing : Imprint: Springer, 2017)
This book is a practical guide to the performance of ultrasonography in women of reproductive age for the diagnosis and treatment of infertility. The coverage includes the use of ultrasonography for evaluation of the various disorders associated with infertility, such as endometriosis, anovulatory disorders, tubal disease, and adenomyosis; its role in assisted reproductive techniques; and its application to assess the viability and early complications of pregnancy. The more recent advances in the field are all addressed, including assessment of ovarian reserve, new classifications of uterine malformations using three-dimensional ultrasonography, and novel ultrasonographic modalities for the evaluation of tubal patency. Within each chapter, the focus is especially on the performance of the ultrasound examination, with highlighting of useful technical tips. The contributors are acknowledged experts from across the world, and the book will be of value for physicians, ultrasonographers, and other medical staff involved in caring for patients with fertility issues.